2009
DOI: 10.1007/s00403-009-0931-0
|View full text |Cite
|
Sign up to set email alerts
|

A cell-based system for screening hair growth-promoting agents

Abstract: Androgen-inducible transforming growth factor beta (TGF-beta1) derived from dermal papilla cells (DPCs) is a catagen inducer that mediates hair growth suppression in androgenetic alopecia (AGA). In this study, a cell-based assay system was developed to monitor TGF-beta1 promoter activity and then used to evaluate the effects of activated TGF-beta1 promoter in human epidermal keratinocytes (HaCaT). To accomplish this, a pMetLuc-TGF-beta1 promoter plasmid that expresses the luciferase reporter gene in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 21 publications
0
36
0
2
Order By: Relevance
“…P2006‐219407A, 2006). However, the procedure is essentially very similar to that previously published (Huh et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…P2006‐219407A, 2006). However, the procedure is essentially very similar to that previously published (Huh et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…In the past, there were a few cell culture-based evidences suggesting that herbal PAK1-blockers such as curcumin, kaempferol, and apigenin from propolis promote the growth of hair cells (Huh et al, 2009). More recently, ARC (artepillin C)-based green propolis from Brazil was shown to promote hair growth in mice (Miyata et al, 2014).…”
Section: Effect On Hair Cell Proliferation In Cell Culturementioning
confidence: 99%
“…[50] 2009 Huh Apigenin stimulated the elongation of hair follicles in a rat vibrissa hair follicle organ culture. [72] and the rate of apoptosis in hair cells differed among cell type in DE [73] (Fig. 4, Table 1).…”
Section: Hanmentioning
confidence: 84%
“…In this study, we sought to demonstrate that a test compound containing LSESr, carnitine and TA represses LPS-activated expression of inflammatory genes using a well-validated in vitro assay representative of HF keratinocytes, specifically, the LPS-stimulated HaCaT cells [16, 17]. We assayed for changes in gene expression across a spectrum of well-characterized inflammatory markers and found that our test compound demonstrates anti-inflammatory properties in vitro .…”
Section: Discussionmentioning
confidence: 99%